Discursos do professor de matemática e suas implicações na compreensão dos alunos - Barboza, Pedro Lucio; Do Rego, Rômulo Marinho; Barbosa, Jonei Cerqueira [UNESP] (FapUNIFESP (SciELO), 2013)
The primary objective of this article is to analyze situations with discursive interactions in math classrooms, which may prompt student's understanding of teacher's speech. To analyze the situations with discursive interactions, this study used elements from Bakhtin's theory of language, mainly its concept of comprehension, and introduces the new concept of intermediate comprehension . The data used in a qualitative approach were collected from class observation through video-recorded lessons. The results showed three situations with discursive interactions that contribute to understanding of the school teacher's speech: 1) speech referring to everyday situations; 2) the teacher's speech math in a less rigorous way 3) teacher comparing different mathematical objects.
Mathematics teacher's speech and its implications in student's understanding
Keywords: Discursive interactions; Student́s understanding; Teacheŕs speech